Computational searching for new stable graphyne structures and their electronic properties. (March 2016) - Kim, Hahn; Kim, Yeonjoon; Kim, Jaewook; Kim, Woo Youn
Abstract: We devised a useful computational strategy to search for new types of stable two-dimensional carbon allotropes. As an illustration, we considered all the isomers of C18 H6 and found three stable building units for graphynes. Then, we investigated the stability of each unit hexagonal/triangular/parallelogrammatic C18 H6 (C18 H6 h /C18 H6 t /C18 H6 p ) in that π-conjugation effects improve the stability and conductivity of the system. The resonance energies of the above C18 H6 are smaller than that of benzene, but still large; among the three types, C18 H6 t is the most stable, followed by C18 H6 p . This supports why the graphyne composed of C18 H6 t was already synthesized, while it is likely that the graphynes composed of C18 H6 h and C18 H6 p could also be synthesized. The graphynes composed of C18 H6 h and C18 H6 p were predicted to have zero band gaps with Dirac cones, whereas that composed of C18 H6 t turned out to be a semiconductor with the band gap of 0.49 eV. In particular, C18 H6 p has not only direction-dependent Dirac cones but also their unconventional locations in the first Brillouin zone.